Indenture Aesthetics - A. Ellapen, Jordache (Duke University Press, 2026)
Jordache A. Ellapen examines the visual and performance art practices of feminist, queer, femme, and gender nonconforming Afro-Indian and South African black artists to understand the paradoxes of freedom in contemporary South Africa.